Pemberdayaan Masyarakat melalui Pelatihan Pengolahan dan Pemanfaatan Bawang Putih Fermentasi untuk Pengobatan Penyakit Degeneratif: Community Empowerment through Training on the Processing and Utilization of Fermented Garlic for the Treatment of Degenerative Diseases - Banne, Yos; Ulaen, Selfie Petronela Joice; Nahor, Evelina Maria (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
People in Silian I Village have a relatively high level of meat consumption, which can trigger various degenerative diseases. To treat their illnesses, people use more modern medicines than traditional medicines. Garlic helps treat various diseases and has been used as a traditional medicine. Fermented Garlic (Black Garlic) has been developed in several countries. The secondary metabolite content in Fermented Garlic is higher than in regular Garlic, so the resulting properties are also more potent. This activity aims to provide training to the public regarding the processing and use of Fermented Garlic (Black Garlic) to treat degenerative diseases. Activities include training on processing Garlic into Fermented Garlic (Black Garlic) and its use in making processed food preparations and counseling regarding licensing procedures for producing processed food. Evaluation of the activity showed increased community knowledge about the processing and use of Black Garlic for treating degenerative diseases after the activity. The community enthusiastically participated in the activity and was interested in making and using it to help treat the degenerative diseases they suffered.